Florid cemento-osseous dysplasia (FCOD): case report - Tai-Min Lin; Wan-Hsuan Huang; Chun-Pin Chiang; Hsiu-Na Lin; Yu-Shu Liao; Meng-Ling Chiang (Elsevier, 2010)
Florid cemento-osseous dysplasia (FCOD) is a type of fibro-osseous lesion and represents a reactive process in which normal bone is replaced by poorly cellularized cementum-like materials and cellular fibrous connective tissues. It is strictly localized to the tooth-bearing or edentulous areas, often occurring bilaterally with symmetric involvements. In this case report, a mixed radiolucent and radiopaque lesion at the periapical area of the right mandibular second molar of a 46-year-old female patient was misdiagnosed as chronic apical periodontitis initially by clinical manifestation and radiographic finding on a periapical radiograph. The tooth #47 was a distal abutment tooth of a three-unit bridge from teeth #45-#47. No decay of teeth #45 and #47 was found when the bridge was removed. Electric pulp test revealed that the tooth #47 was a vital-pulp tooth. Panoramic radiography showed a similar mixed radiolucent and radiopaque lesion at the edentulous area of tooth #37. The symmetric distribution of the two lesions with no alveolar bone expansion and the positive vitality test of the involved tooth supported the diagnosis of FCOD for this case. No endodontic treatment or surgical biopsy was performed. The patient was instructed to undergo regular clinical and radiographic follow-up to monitor the change of the lesion. We suggest that when a radiolucent or mixed lesion occurs at the periapical area of a vital-pulp tooth, panoramic radiography may help differentiate an inflammatory periapical lesion from a lesion of cemento-osseous dysplasia (COD).